Development of Fluorinated Thienylchalcones as Monoamine Oxidase-B Inhibitors: Design, Synthesis, Biological Evaluation and Molecular Docking Studies - Mathew, Bijo; Ucar, Gulberk; Yabanogclu-Ciftci, Samiye; Baysal, Ipek; Suresh, Jerad; Elizabeth Mathew, Githa; Kunjumon Vilapurathu, Jobin; M. Nadeena, A.; Nabeela, P.; Lakshmi, V.; Haridas, Abitha; Fathima, Fajeelath (Letters in Organic Chemistry, 2015)
A series of thienylchalcones with fluoro and trifluoromethyl derivatives were synthesized and evaluated for their capability to inhibit human monoamine oxidase A and B. The chemical structures of the compounds have been ascertained by means of their 1HNMR, 13CNMR, mass spectroscopic data and elemental analysis. The results documented that these compounds revealed moderate to good inhibitory activities towards MAO-B than MAO-A. The most active compound, (2E)-1-(thiophen-2-yl)-3-[4-(trifluoromethyl) phenyl] prop-2-en-1-one exhibited with Ki value for MAO-B of 0.90 ± 0.05 µM with a 5-fold selectivity for MAO-B over the MAO-A isoform. All the fluorinated thienylchalcones under the present study showed as reversible inhibitors, while kinetic analysis revealed a competitive mode of binding. Molecular docking studies were executed to further explain the in vitro results of the new compounds, and to establish the hypothetical binding poses for the compounds inside the inhibitor binding cavity of hMAO-B.
Keywords: thienylchalcones